THE LEGAL STATUS OF ARTISTIC WORKS CREATED BY GENERATIVE ARTIFICIAL INTELLIGENCE FROM THE PERSPECTIVE OF INDONESIAN COPYRIGHT LAW - Made Ardia; Yenny Eta Widyanti; Djumikasih (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The development of Generative Artificial Intelligence (AI) has produced new forms of artistic works that generate uncertainty within Indonesia’s copyright law regime. Law Number 28 of 2014 on Copyright continues to position humans as the sole legal subjects eligible to be recognized as authors, thereby rendering works created entirely by AI unable to satisfy the requirements of originality and human authorship. The disparity between technological advancements and existing legal norms has resulted in regulatory gaps, particularly concerning the legal status of copyright holders and the scope of legal protection for generative AI based artistic works. Through normative juridical research, this study examines the necessity of legal reconstruction to accommodate this phenomenon without disregarding the foundational principles of copyright protection. The findings indicate that human intellectual contribution remains the essential basis for recognizing artistic works assisted by generative AI, while current regulations have yet to provide adequate legal certainty. Therefore, regulatory reforms that are adaptive and humanistic are required to ensure that legal protection remains relevant and equitable in the era of generative AI development.